Troponina T em mulheres com e sem diabetes mellitus gestacional: estudo longitudinal - Tairova, Ekaterina Stanislavovna (My University, 2025)
High-sensitivity cardiac troponin T (hs-TnT) is a well-established biomarker of myocardial injury. While hyperglycemia is associated with subclinical myocardial stress, little is known about hs-TnT dynamics during pregnancy, particularly in women with gestational diabetes mellitus (GDM). We investigated the longitudinal concentration changes in hs-TnT levels in pregnant women with and without GDM. In this prospective observational cohort study, we included 97 pregnant women (56 with GDM and 41 controls) recruited between July 2021 and December 2023. Hs-TnT levels, glycemic and lipid profiles, and clinical parameters were measured at three timepoints: T0 (24-28 gestational weeks), T1 (> 34 weeks), and T2 (3-6 months postpartum). Hs-TnT levels were detected by an electrochemiluminescence immunoassay. Data was analyzed with longitudinal quantile mixed models at the 0.05, 0.50, and 0.95 quantiles. Of the 97 participants, 73 completed follow-up. Hs-TnT levels increased significantly over time in women with higher baseline hs-TnT (upper quantile) during pregnancy and postpartum (T = 0.95; ß = 1.69 × 10-; p = 0.00002). No statistically significant differences in hs-TnT levels were observed between the GDM and control groups. Glycated hemoglobin showed a consistent, although non-significant, positive association with hs-TnT across all quantiles. In patients with high baseline troponin concentrations, hs-TnT levels rise throughout gestation and persist postpartum, regardless of GDM diagnosis. The absence of group differences may reflect effective glycemic control in the GDM cohort. These findings highlight the potential role of hs-TnT as a biomarker of early cardiac damage in pregnancy. [resumo fornecido pelo autor]
A troponina T cardíaca ultrassensível (cTnT-us ) é um biomarcador bem estabelecido de lesão miocárdica. Embora a hiperglicemia esteja associada ao estresse miocárdico subclínico, pouco se sabe sobre a dinâmica da cTnT-us durante a gestação, especialmente em mulheres com diabetes mellitus gestacional (DMG). Este estudo investigou as variações longitudinais das concentrações de cTnT-us em gestantes com e sem DMG. Neste estudo de coorte prospectivo e observacional, foram incluídas 97 gestantes (56 com DMG e 41 controles) recrutadas entre julho de 2021 e dezembro de 2023. Os níveis de cTnT-us , perfis glicêmico e lipídico e parâmetros clínicos foram avaliados em três momentos: T0 (24-28 semanas de gestação), T1 (< 34 semanas) e T2 (3-6 meses pós-parto). A cTnT-us foi quantificada por imunoensaio de eletroquimioluminescência. Os dados foram analisados por modelos longitudinais de regressão quantílica mista nos quantis 0,05, 0,50 e 0,95. Das 97 participantes, 73 completaram o seguimento. Os níveis de cTnT-us aumentaram significativamente ao longo do tempo em mulheres com valores basais mais elevados (quantil superior) durante a gestação e no pós-parto (T = 0,95; ß = 1,69 × 10- ; p = 0,00002). Não foram observadas diferenças estatisticamente significativas nos níveis de cTnT-us entre os grupos DMG e controle. A hemoglobina glicada apresentou associação positiva consistente, embora não significativa, com cTnT-us em todos os quantis. Em mulheres com concentrações basais mais altas de troponina, os níveis de hs-TnT aumentam ao longo da gestação e permanecem elevados no pós-parto, independentemente do diagnóstico de DMG. A ausência de diferenças entre os grupos pode refletir um adequado controle glicêmico na coorte com DMG. Esses achados sugerem o potencial da hs-TnT como biomarcador de lesão cardíaca precoce durante a gestação. [resumo fornecido pelo autor]
Keywords: Diabetes na gravidez; Troponina T; Grávidas - Doenças; Biomarcadores; Coração - Doenças; Diabetes in pregnancy; Troponin T; Pregnant women - Diseases; Biomarkers; Heart - Diseases